2017
DOI: 10.1038/ncomms14774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlation between amyotrophic lateral sclerosis and schizophrenia

Abstract: We have previously shown higher-than-expected rates of schizophrenia in relatives of patients with amyotrophic lateral sclerosis (ALS), suggesting an aetiological relationship between the diseases. Here, we investigate the genetic relationship between ALS and schizophrenia using genome-wide association study data from over 100,000 unique individuals. Using linkage disequilibrium score regression, we estimate the genetic correlation between ALS and schizophrenia to be 14.3% (7.05–21.6; P=1 × 10−4) with schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 39 publications
6
90
1
1
Order By: Relevance
“…We found that pimozide is safe and tolerable at doses up to 4 mg/day and demonstrated preliminary evidence of target engagement at the NMJ. It has been proposed that prolonged use of antipsychotic medications may protect against ALS (45) and a recent report has shown a genetic link between ALS and schizophrenia, supporting the idea that neuroleptics may be effective in treating ALS (46). The next RCT of pimozide in 100 subjects with ALS began recruitment in November 2017 (ClinicalTrials.gov; NCT03272503) and will further examine pimozide's effects on safety, tolerability, clinical outcome measures, and RNS in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…We found that pimozide is safe and tolerable at doses up to 4 mg/day and demonstrated preliminary evidence of target engagement at the NMJ. It has been proposed that prolonged use of antipsychotic medications may protect against ALS (45) and a recent report has shown a genetic link between ALS and schizophrenia, supporting the idea that neuroleptics may be effective in treating ALS (46). The next RCT of pimozide in 100 subjects with ALS began recruitment in November 2017 (ClinicalTrials.gov; NCT03272503) and will further examine pimozide's effects on safety, tolerability, clinical outcome measures, and RNS in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) are rapidly identifying loci affecting multiple phenotypes. 1,2 Moreover, using cross-trait versions of methods such as genomic-relatedness-based restricted maximum-likelihood (GREML) 3 and LD-score regression (LDSC) 4 researchers have identified genetic correlations between diverse traits, e.g., polycystic ovary syndrome and pubertal timing, 5 amyotrophic lateral sclerosis (ALS) and schizophrenia, 6 and anorexia nervosa and obsessive-compulsive disorder. 7 More generally, these analyses are suggestive of constellations of phenotypes affected by shared sources of genetic liability, but they do not permit the causes of the observed genetic correlations to be investigated systematically.…”
Section: Genomic Structural Equation Modelingmentioning
confidence: 99%
“…We also identified five gene sets showing the opposite pattern, i.e., smaller expression variance in SCZ than CTL. Among these five, two gene sets contain largely overlapped genes encoding proteins of the survival motor neuron (SMN) complex, which plays a role in neuronal migration and differentiation (Giavazzi et al 2006), with a potential role in SCZ (Comley et al 2016;McLaughlin et al 2017). One gene set consists of genes that encode synaptic cell adhesion proteins, interacting with neurexins, which is essential for brain function (Missler et al 2012).…”
Section: Overdispersed Expression In Gene Setsmentioning
confidence: 99%